2019
DOI: 10.1002/hep.30839
|View full text |Cite
|
Sign up to set email alerts
|

Type 3 Inositol 1,4,5‐Trisphosphate Receptor Is Increased and Enhances Malignant Properties in Cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is the second most common malignancy arising in the liver. It carries a poor prognosis, in part because its pathogenesis is not well understood. The type 3 inositol 1,4,5‐trisphosphate receptor (ITPR3) is the principal intracellular calcium ion (Ca2+) release channel in cholangiocytes, and its increased expression has been related to the pathogenesis of malignancies in other types of tissues, so we investigated its role in CCA. ITPR3 expression was increased in both hilar and intrahepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 55 publications
3
55
0
Order By: Relevance
“…Transmission of calcium into mitochondria depends on which ITPR isoforms are expressed at the MAM, ( 15,16 ) which varies among cell types and can change in disease states. ( 13,14,17,18 ) Therefore, we examined whether expression of each of the three ITPR isoforms was altered in YF.…”
Section: Resultsmentioning
confidence: 99%
“…Transmission of calcium into mitochondria depends on which ITPR isoforms are expressed at the MAM, ( 15,16 ) which varies among cell types and can change in disease states. ( 13,14,17,18 ) Therefore, we examined whether expression of each of the three ITPR isoforms was altered in YF.…”
Section: Resultsmentioning
confidence: 99%
“…An increased expression of ITPR3 was detected in clear renal cell carcinoma compared to the unaffected part of the kidney [81]; ITPR3 silencing affected tumor growth, in vitro as well as in vivo, providing a direct proof of the involvement of this receptor in the carcinogenesis. An increased expression of ITPR3 has been also observed in cholangiocarcinoma [82] and in colorectal cancer [83]; in both cases the expression of ITPR3 correlated with the degree of neoplasia severity [82,83].…”
Section: Itprs and Cancermentioning
confidence: 87%
“…These signaling pathways included the role of Ca 2+ in the hormonal regulation of glycolysis and one of the first observations of Ca 2+ oscillations in animal cells [ 43 , 44 ]. Likewise, intracellular Ca 2+ -signaling in cholangiocytes was well characterized (reviewed in [ 45 , 46 ]). However, much less is known about intracellular Ca 2+ -signaling in Kupffer, stellate and sinusoidal endothelial cells.…”
Section: Role Of Intracellular Ca 2+ In Regulatmentioning
confidence: 99%
“…Two recent studies have shown that Ca 2+ release from the ER through InsP 3 R3 mediates the progression of both HCC and cholangiocarcinoma [ 33 , 46 ]. In hepatocytes isolated from normal human liver, expression of InsP 3 R3 was found to be very low or not detectable.…”
Section: Type 3 Insp 3 Receptors In the Progrementioning
confidence: 99%
See 1 more Smart Citation